Introduction to LGBTQ+ Studies A Cross-Disciplinary Approach - Amory, Deborah P.; Massey, Sean G.; Miller, Jennifer; Brown, Allison P. (Open textbook library., 2023)
Designed for an introductory course, this textbook takes a cross-disciplinary approach to the study of LGBTQ+ issues that helps students grasp core concepts through a variety of different perspectives. Introduction to LGBTQ+ Studies offers accessible, academically sound information on a wide range of topics, including history, culture, and Queer Theory; an exploration of LGBTQ+ relationships, families, parenting, health, and education; and how to conduct research on LGBTQ+ topics. The book explores LGBTQ+ issues from the ancient world to contemporary global perspectives. Employing an intersectional analysis, the textbook highlights how sexuality and gender are simultaneously experienced and constructed through other structures of inequality and privilege, such as race and class. The text supports multiple learning styles by integrating visual elements, multimedia resources, discussion and project prompts, and resources for further research throughout the textbook.